Dendrometer and meteorological data from the TreeNet network, year 2003 - Roman Zweifel; Frank J Sterck; Sabine Braun; Nina Buchmann; Werner Eugster; Arthur Gessler; Matthias Haeni; Richard L Peters; Lorenz Walthert; Micah Wilhelm; Kasia Ziemínska; Sophia Etzold (PANGAEA, 2021)
The timing of diel stem growth of mature forest trees is still largely unknown, as empirical data with high temporal resolution have not been available so far. Consequently, the effects of day-night conditions on tree growth remained uncertain. Here we present the first comprehensive field study of hourly-resolved radial stem growth of seven temperate tree species, based on 57 million underlying data points over a period of up to 8 years. We show that trees grow mainly at night, with a peak after midnight, when the vapour pressure deficit (VPD) is among the lowest. A high VPD strictly limits radial stem growth and allows little growth during daylight hours, except in the early morning. Surprisingly, trees also grow in moderately dry soil when the VPD is low. Species-specific differences in diel growth dynamics show that species able to grow earlier during the night are associated with the highest number of hours with growth per year and the largest annual growth increment. We conclude that species with the ability to overcome daily water deficits faster have greater growth potential. Furthermore, we conclude that growth is more sensitive than carbon uptake to dry air, as growth stops before stomata are known to close.
In: Zweifel, R et al. (2021): Dendrometer and meteorological data from the TreeNet network (1997-2018) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.935394